2 - Les relations économiques Brésil-Afrique dans le contexte des rapports internationaux - d'ADESKY, Jacques (Africa Development, 1984)
The «centre of gravity» of world power is located very high in the Northern hemisphere. This situation reflects North-South power relations. However South-South relations aim, among other things, at changing basic fact in today's international relations by ģiving preference to peri- pheral relations. The development of economic relations between Brazil and Africa shows that South-South relations are indeed a fact. It obviously does not imply a new division of markets into separate geographic zones which would ultimately break the international division of labour. Both Brazil and Africa are still economically subordinated to developed countries and in maintaining peripheral relations, they implicitly recognize that they not in complete control of these relations. As a matter of fact these peri- pheral relations fit into their dependence links with the world market which forces its demands and its rules on them. Henceforth Third World countries do not control the peripheral model that they wish to have. External elements thwart their wills as these elements tend to see South- South relations as playing a purely upsetting role. Developing countries are therefore confined in a vicious circle which is uneasy to break. Confronted with such a complex reality, we did not expect to raise all the issues concerning the problematic of economic relations between Brazil and Africa, in this article. We simply considered points which appeared essential to grasp these relations as being a modern form of peripheral exchange with a possibility to lead to further autonomy from the North without, however, giving rise to domination and destruc- tion among unequally developed « Southern » partners